2014
DOI: 10.1002/hbm.22677
|View full text |Cite
|
Sign up to set email alerts
|

Predictive distractor context facilitates attentional selection of high, but not intermediate and low, salience targets

Abstract: It is well established that we can focally attend to a specific region in visual space without shifting our eyes, so as to extract action-relevant sensory information from covertly attended locations. The underlying mechanisms that determine how fast we engage our attentional spotlight in visual-search scenarios, however, remain controversial. One dominant view advocated by perceptual decision-making models holds that the times taken for focal-attentional selection are mediated by an internal template that bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 61 publications
7
30
0
Order By: Relevance
“…Besides these methodological prerequisites, in a series of studies, we have reliably found that the saliency of the target is, in fact, one of the key factors that influence the PCN signal strength. In particular, we found the PCN to be gradually amplified as a function of the target's increasing physical dissimilarity relative to the distractor items . On the basis of this pattern, we proposed a saliency‐based filtering mechanism to underlie the PCN (difference) wave, which would essentially integrate both target selection and distractor suppression.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Besides these methodological prerequisites, in a series of studies, we have reliably found that the saliency of the target is, in fact, one of the key factors that influence the PCN signal strength. In particular, we found the PCN to be gradually amplified as a function of the target's increasing physical dissimilarity relative to the distractor items . On the basis of this pattern, we proposed a saliency‐based filtering mechanism to underlie the PCN (difference) wave, which would essentially integrate both target selection and distractor suppression.…”
Section: Discussionmentioning
confidence: 81%
“…In particular, we found the PCN to be gradually amplified as a function of the target's increasing physical dissimilarity relative to the distractor items. 35,45 On the basis of this pattern, we proposed a saliencybased filtering mechanism to underlie the PCN (difference) wave, which would essentially integrate both target selection and distractor suppression. In brief, we suggest that the PCN signal may represent the target's saliency signal at the level of the attention-guiding master map-as envisaged by guided search-type models.…”
Section: Orienting Attention To Locations In Visual Versus Mental Spamentioning
confidence: 99%
“…Only a few studies have used the N2pc to study automatic processes of attention to Gestalt stimuli (Conci et al, 2006, 2011; Töllner et al, 2015; Wiegand et al, 2015), while other studies were not appropriate for studying the N2pc either because non-lateralized visual stimuli were used (Han et al, 2005) or because sensory information was not balanced across hemifields (Kasai et al, 2011). Both requirements need to be satisfied in the design of a proper N2pc study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Töllner, Zehetleitner, Gramann, and Müller (2011) confirmed the PCN's change in concert with the salience of a visual stimulus using systematic variations in a target's salience level. As they changed the salience of the target in a visual search task from high to low (through varying either target orientation away from horizontal or varying the contrast of a single color), the latency of the PCN increased and the amplitude decreased (see also Töllner, Conci, & Müller, 2015, for similar PCN effects for shape-defined targets). This finding suggests that the PCN is likely to reflect target salience in visual pop-out searches with physically balanced, bilateral displays.…”
Section: Introductionmentioning
confidence: 97%